Mutations and Polymorphisms in the Human Argininosuccinate Lyase (ASL) Gene. Issue 1 (25th November 2013) - Balmer, Cécile; Pandey, Amit V.; Rüfenacht, Véronique; Nuoffer, Jean‐Marc; Fang, Ping; Wong, Lee‐Jun; Häberle, Johannes
<x xml:space="preserve">Abstract</x> Argininosuccinate lyase deficiency (ASLD) is an inborn error of metabolism caused by a defect of the urea cycle enzyme argininosuccinate lyase (ASL) encoded by the ASL gene. Patients are affected by life‐threatening hyperammonemia, mental retardation and liver disease. We are providing here an update on the molecular basis of this disease by presenting all today known mutations (n = 134) as well as all known different genotypes (n = 160). To illustrate these data, we are presenting structural considerations focussing on the relevance of the known mutations for ASL homotetramer formation and function. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>